Wages and recruitment: Evidence from external wage changes - Torberg Falch (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper estimates the causal effect of the wage on the recruitment rate at the establishment level. During the 1990s, the wage setting for certified teachers in Norway was completely centralized, with a wage premium of about 10 percent at schools with severe recruitment problems in the past and located in one specific region. The empirical approach exploits within-school variation in wage premium eligibility and that teacher supply is observed at these schools with excess demand for teachers. In a difference-in-differences framework, I find that the wage premium increased the recruitment rate by 6-7 percentage points. The finding is robust to model specification and sample, but larger for young teachers than old teachers. The results indicate that the short-run labor supply elasticity towards the individual establishment is about 1.4.
Keywords: J22; J45; 330; recruitment; wages; labor supply; teacher mobility; Lehrkräfte; Personalbeschaffung; Lohnniveau; Arbeitsangebot; Arbeitsmobilität; Norwegen